Challenges in Education and Need for Transformation with Possible Solutions - Kakumanudi, Lakshmi (Journal of Engineering Education Transformations, 2018)
The goal of my paper is to focus on teaching and learning practices and lead students to move with clear objectives with practicality for their bright career. They are graduating without much practical experience as per the need of the current society. The very purpose of this IUCEE dais is to find needs in education and share possible practices to find solutions for better teaching, learning, and implementation. Collaborative learning practices in our college gave a visible change in the results from the first mid to second mid exams; the need for such practices in many practical achievements is discussed. This paper has also presented various practices of collaborative learning at our college and out puts for the extracurricular and co-curricular activities. At the same time how the success in other activities is inter linked with the academic success of the students by increasing their confidence level. The direct and indirect reflection of the success, can it be continued leading to good career and campus placements. Various practices are discussed with objectives and out puts and also tried to visualize by showing pictures of those practices at our college.